Colheita, beneficiamento e controle de qualidade de sementes de nabo forrageiro - Nery, Marcela Carlota (2008)
The fodder radish Raphanus sativus L. var oleiferus Mstzg., is a culture with potential to be used for the production of biodiesel, due to its grains being composed of 30 to 43% oil. Aiming to expand the cultivation of this species, the use of high quality seeds is necessary, however, research related to seed harvest and post-harvest, and an appropriate methodology to evaluate seed quality are still scarce. In order to verify the best conditions to execute the germination test, sand and paper were tested as substrates, and the seeds were maintained under six constant temperature regimes (15° C; 20° C; 25° C; 30° C; 35° C) and one alternating (20° C-30° C). In order to verify the allelopathic effect of the culture, lettuce and fodder radish seeds were germinated in plant extracts and fodder radish seedlings. To evaluate the plant vigor the following methodologies were used: the electrical conductivity test (imbebition during 2; 4; 6; 8; 10 and 12 hours, using 25 seeds in 25 mL and 50 mL, 50 seeds in 50 mL and 75 mL of water), accelerated aging (traditional methodology and with a saturated NaCl solution during 0; 24; 48; 72 and 96 hours) and the tetrazolium test, at 25° C, during 3 h; 12 h and 18 hours). The effects of the processing steps on the seed quality were evaluated through tests and determinations, such as different moisture content, purity, weight per one thousand seeds, germination, first germination count, germination speed index, initial stand, emergence, emergence speed index, seedling aerial part dry matter and health quality. To investigate the effect of the harvesting stage on physical, physiological and health quality, the siliques were harvest at three stages, according to their green, beige and brown color. The seeds were stored in a cold chamber and at room temperature, evaluations were carried out in 0; 3; 6 and 9 months. It was concluded that the temperature of 20° C- 30° C and the sand substrate were the most appropriate conditions to carry out the germination test of fodder radish seeds. The fodder radish does not cause a reduction of seed germination within their own culture. The imbebition period of 6 hours with 25 seeds in 50 mL of distilled and deionized water is considered appropriate to evaluate the fodder radish seed physiological quality using the electrical conductivity test. The accelerated aging test allows for the separation of fodder radish seed lots at different quality levels, the use of a 96 hour aging period by the traditional method or 72 hours with a saturated NaCl solution being possible. In the tetrazolium test the seed imbebition between paper for 6 hours, followed by a longitudinal cut is effective to evaluate the fodder radish seed viability. It is still necessary to test intermediate concentrations between 0.075% and 0.5%, since with 0.075%, the seeds stained weakly and with 0.5% the test results were overestimated. The processing in an air screen separator and gravity table set at high discharge contributes to the improvement of the fodder radish seed physical and physiological quality, with an average increase of up to 25% in purity and 9% in germination and emergence, according to the comparison of the results with the non-processed seeds. The silique color is not the ideal indicator to define the fodder radish seed harvesting time because of the variation in the maturity and physiological quality of fodder radish seeds within siliques. The fodder radish seed storage in cold chamber favors the seedlings emergence. There were no consistent changes in the centesimal composition of fodder radish siliques harvested at different stages of maturity related to their different colors.